Removable pressure-sensitive adhesive composition, surface protection film, and optical member with pressure-sensitive adhesive layer

The described pressure-sensitive adhesive composition, with its specific polymer structure and composition, addresses the challenge of reducing adhesive strength during high-speed peeling while maintaining good wetting properties, effectively solving the issues faced by existing adhesive compositions.

JP7650551B1Active Publication Date: 2025-03-25SAIDEN CHEM IND
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
JP2024117208
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2025-03-25
Estimated Expiration
2044-07-22

AI Technical Summary

Technical Problem

Existing pressure-sensitive adhesive compositions for surface protective films on optical members face challenges in reducing adhesive strength during high-speed peeling while maintaining good wetting properties and avoiding increased adhesive strength during slow peeling.

Method used

A releasing pressure-sensitive adhesive composition comprising a (meth)acrylic polymer (A) with a specific structure, including 20 to 85% by mass of n-octyl acrylate, 1.5 to 14.5% by mass of a functional group-containing polymerizable monomer, and 5 to 25% by mass of polyalkylene glycol chain-containing mono(meth)acrylate, with an acid value of 7.5 mg KOH/g or less.

Benefits of technology

The adhesive composition achieves excellent wetability and reduces adhesive strength during both slow and high-speed peeling, while maintaining adequate wetting properties and preventing increased adhesive strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007650551000001
    Figure 0007650551000001
  • Figure 0007650551000002
    Figure 0007650551000002
  • Figure 0007650551000003
    Figure 0007650551000003
Patent Text Reader

Abstract

An object of the present invention is to provide a removable pressure-sensitive adhesive composition that has excellent wettability and reduces adhesive strength during low-speed and high-speed peeling. [Solution] The (meth)acrylic polymer (A) comprises 85 to 98.5 mass % of an alkyl group-containing unsaturated monomer (a1) having an alkyl group of 1 to 18 carbon atoms and 1.5 to 15 mass % of a polymerizable monomer (a2) having a functional group, wherein the alkyl group-containing unsaturated monomer (a1) having an alkyl group of 1 to 18 carbon atoms contains at least n-octyl acrylate, and the (meth)acrylic polymer (A) has an acid value of 7.5 mg KOH / g or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a removable pressure-sensitive adhesive composition, a surface protective film, and an optical member with a pressure-sensitive adhesive layer. [Background technology]

[0002] In the manufacturing process of optical members (e.g., polarizing plates) constituting liquid crystal displays, surface protection films are attached to the optical members to temporarily protect the surfaces of the optical members. The surface protection films are peeled off from the optical members by users after use, so the surface protection films have a slightly adhesive layer. Recently, with the increase in size of liquid crystal displays, the size of surface protection films for optical members has also increased. In general, the larger the size of the surface protection film, the more difficult it is to quickly peel the surface protection film off the optical members. For this reason, there is a demand for surface protection films to have a reduced adhesive force during high-speed peeling. There is also a demand for the adhesive layer to have good wettability that allows it to sufficiently wet the surface of the adherend (the cut end does not turn up when cut).

[0003] Therefore, Patent Documents 1 and 2 propose a pressure-sensitive adhesive composition containing 2-ethylhexyl acrylate and a copolymerizable vinyl monomer containing a functional group. Patent Documents 3 and 4 propose a pressure-sensitive adhesive containing n-octyl acrylate and acrylic acid. Patent Documents 5 and 6 propose a surface protection film having a pressure-sensitive adhesive layer formed by crosslinking a pressure-sensitive adhesive composition containing 2-ethylhexyl acrylate and n-octyl acrylate. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 63-225677 [Patent Document 2] JP 2023-133557 A [Patent Document 3] Patent No. 6607330 [Patent Document 4] Patent No. 7338444 [Patent Document 5] JP 2023-160818 A [Patent Document 6] JP 2020-183460 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, in Patent Documents 1 and 2, the crosslink density of the adhesive layer needs to be increased to reduce the adhesive strength during high-speed peeling, but wettability decreases. In Patent Documents 3 and 4, the acid value of the acrylic copolymer is high, the polarity of the adhesive layer is high, and the intermolecular force with the adherend surface is strong, so the adhesive strength during low-speed and high-speed peeling cannot be reduced. In Patent Documents 5 and 6, the content of n-octyl acrylate is low, so the adhesive strength during low-speed peeling cannot be reduced. In addition, wettability deteriorates.

[0006] Therefore, an object of the present invention is to provide a removable pressure-sensitive adhesive composition that has excellent wettability and reduces adhesive strength during low-speed and high-speed peeling. [Means for solving the problem]

[0007] In order to achieve the object of the present invention, the removable pressure-sensitive adhesive composition of the present invention has the following configuration: That is, the composition comprises a (meth)acrylic polymer (A) containing, as structural units, an alkyl group-containing unsaturated monomer (a1) having an alkyl group with 1 to 18 carbon atoms and 1.5 to 14.5 mass % of a polymerizable monomer (a2) having a functional group, the alkyl group-containing unsaturated monomer (a1) having an alkyl group with 1 to 18 carbon atoms contains 20 to 85 mass % of n-octyl acrylate, and the acid value of the (meth)acrylic polymer (A) is 7.5 mg KOH / g or less. The (meth)acrylic polymer (A) further contains 5 to 25 mass % of a polyalkylene glycol chain-containing mono(meth)acrylate (a3) ​​as a constituent unit, wherein the polyalkylene glycol chain-containing mono(meth)acrylate (a3) ​​having at least one hydroxy group does not belong to the polymerizable monomer (a2) having a functional group, and the polyalkylene glycol chain-containing mono(meth)acrylate (a3) ​​is methoxypolyethylene glycol methacrylate. Effect of the Invention

[0008] According to the present invention, it is possible to provide a removable pressure-sensitive adhesive composition that has excellent wettability and reduces adhesive strength during low-speed and high-speed peeling. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The following embodiments are described in detail. Note that the following embodiments do not limit the scope of the invention, and not all of the combinations of features described in the embodiments are essential to the invention. Two or more of the features described in the embodiments may be combined in any combination.

[0010] In this specification, the expression "A to B" expressing a range of numerical values ​​is synonymous with "A or more" and "B or less," and includes A and B.

[0011] As used herein, the term "(meth)acrylic" refers to both "acrylic" and "methacrylic." Additionally, the term "(meth)acrylate" refers to both "acrylate" and "methacrylate."

[0012] The monomer component that is the constituent unit of the (meth)acrylic polymer (A) can be one or more of monomers having a polymerizable unsaturated bond (hereinafter, sometimes referred to as "polymerizable monomers"). The (meth)acrylic polymer (A) is preferably a copolymer of two or more polymerizable monomers.

[0013] <Removable Adhesive Composition> The removable pressure-sensitive adhesive composition according to one embodiment contains at least a (meth)acrylic polymer (A). In this specification, removable property refers to a property including ease of removal and less adhesive residue when a surface protective film having a pressure-sensitive adhesive layer made of the removable pressure-sensitive adhesive composition is attached to various adherends and then peeled off after a certain period of time.

[0014] <(Meth)acrylic polymer (A)> The (meth)acrylic polymer (A) according to one embodiment comprises 85-98.5% by mass of an alkyl group-containing unsaturated monomer (a1) having an alkyl group of 1-18 carbon atoms and 1.5-15% by mass of a polymerizable monomer (a2) having a functional group. Here, the alkyl group-containing unsaturated monomer (a1) having an alkyl group of 1-18 carbon atoms contains at least n-octyl acrylate. The alkyl group-containing unsaturated monomer (a1) having an alkyl group of 1-18 carbon atoms may further contain a monomer other than n-octyl acrylate in addition to n-octyl acrylate. In this case, it is sufficient that the content of n-octyl acrylate is greater than the content of the monomer other than n-octyl acrylate. In other words, the type and content of the monomer other than n-octyl acrylate are not particularly limited as long as they are within the range in which the above relationship is satisfied. The acid value of the (meth)acrylic polymer (A) is 7.5 mg KOH / g or less. The acid value is a calculated value obtained from the charged amount of the polymerizable monomer having a carboxy group used in producing the (meth)acrylic polymer (A).

[0015] The (meth)acrylic polymer (A) according to one embodiment contains, as structural units, an alkyl group-containing unsaturated monomer (a1) having an alkyl group with 1 to 18 carbon atoms, and 1.5 to 14.5 mass % of a polymerizable monomer (a2) having a functional group. Here, the alkyl group-containing unsaturated monomer (a1) having an alkyl group with 1 to 18 carbon atoms contains 20 to 85 mass % of n-octyl acrylate. The acid value of the (meth)acrylic polymer (A) is 7.5 mg KOH / g or less. The acid value is a calculated value obtained from the charged amount of the polymerizable monomer having a carboxy group used in producing the (meth)acrylic polymer (A).

[0016] Here, the acid value is a parameter indicating the amount of an acidic functional group called a carboxy group. More specifically, the acid value refers to the number of milligrams of potassium hydroxide required to neutralize the free fatty acid contained in 1 g of a sample (unit: mg KOH / g). The acid value can be adjusted based on the blending amount of a polymerizable monomer having a carboxy group, which will be described later. The upper limit of the acid value of the (meth)acrylic polymer (A) is 7.5 mg KOH / g or less, 7.4 mg KOH / g or less, 7.3 mg KOH / g or less, 7.2 mg KOH / g or less, 7.1 mg KOH / g or less, 7.0 mg KOH / g or less, 6.9 mg KOH / g or less, 6.8 mg KOH / g or less, 6.7 mg KOH / g or less, 6.6 mg KOH / g or less, 6.5 mg KOH / g or less, 6.4 mg KOH / g or less, and preferably 6.3 mg KOH / g or less, from the viewpoint of reducing the adhesive strength during low-speed and high-speed peeling. In this specification, the lower limit of the acid value of the (meth)acrylic polymer (A) includes 0 mg KOH / g. The lower limit of the acid value is 0 mg KOH / g or more, 0.1 mg KOH / g or more, 0.2 mg KOH / g or more, 0.3 mg KOH / g or more, 0.4 mg KOH / g or more, 0.5 mg KOH / g or more, 0.6 mg KOH / g or more, 0.7 mg KOH / g or more, 0.8 mg KOH / g or more, 0.9 mg KOH / g or more, 1.0 mg KOH / g or more, 1.5 mg KOH / g or more, 2.0 mg KOH / g, 2.5 mg KOH / g or more, or 3.0 mg KOH / g or more. The range of the acid value may be a combination of any of the lower limit and upper limit values ​​described above. In addition, when the acid value of the (meth)acrylic polymer (A) exceeds 7.5 mg KOH / g, the adhesive strength during low-speed and high-speed peeling is high.

[0017] <Alkyl-containing unsaturated monomer (a1) having an alkyl group having 1 to 18 carbon atoms> Examples of the alkyl group-containing unsaturated monomer (a1) having an alkyl group having 1 to 18 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, sec-butyl (meth)acrylate, n-amyl (meth)acrylate, isoamyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 1-methylheptyl (meth)acrylate, n-nonyl (meth)acrylate, Examples of the (meth)acrylic acid alkyl esters having a linear or branched alkyl group such as n-butyl (meth)acrylate, ... Moreover, the alkyl group-containing unsaturated monomer (a1) having an alkyl group having 1 to 18 carbon atoms may further contain 2-ethylhexyl acrylate.

[0018] The content of n-octyl acrylate according to one embodiment is preferably 85 to 98.5% by mass based on 100% by mass of the total polymerizable monomers. The upper limit of the content of n-octyl acrylate is 98.5% by mass or less, 98% by mass or less, 97.5% by mass or less, 97% by mass or less, 96.5% by mass or less, 96% by mass or less, 95.5% by mass or less, 95% by mass or less, 94.5% by mass or less, or 94.2% by mass or less. The lower limit of the content of n-octyl acrylate is 85% by mass or more, 86% by mass or more, 87% by mass or more, 88% by mass or more, 89% by mass or more, or 90% by mass or more. When the content of n-octyl acrylate is within the above-mentioned range, the adhesive strength during low-speed and high-speed peeling can be reduced. On the other hand, if the content of n-octyl acrylate exceeds 98.5% by mass or is less than 85% by mass, the adhesive strength during low and high speed peeling increases.

[0019] The content of n-octyl acrylate according to one embodiment is preferably 20 to 85% by mass relative to 100% by mass of all polymerizable monomers when the (meth)acrylic polymer (A) contains a monomer other than n-octyl acrylate as a constituent unit as the (a1) component. The upper limit of the content of n-octyl acrylate is 85% by mass or less, 84% by mass or less, 83% by mass or less, 82% by mass or less, 81% by mass or less, or 80% by mass or less. The lower limit of the content of n-octyl acrylate is 20% by mass or more, 25% by mass or more, 30% by mass or more, 35% by mass or more, 40% by mass or more, 45% by mass or more, or 50% by mass or more. The range of the content of n-octyl acrylate may be a combination of any of the lower limit and upper limit values ​​described above. When the content of n-octyl acrylate is within the above-mentioned predetermined range, the adhesive strength during low-speed and high-speed peeling can be reduced, and good wettability can be obtained. On the other hand, if the content of n-octyl acrylate is less than 20% by mass, the adhesive strength during low-speed peeling increases and the wettability decreases.

[0020] In one embodiment, when the (meth)acrylic polymer (A) contains n-octyl acrylate as a constituent unit, the content of the monomer other than n-octyl acrylate is preferably 0.5 to 78% by mass relative to 100% by mass of all polymerizable monomers. The upper limit of the content of the monomer other than n-octyl acrylate is 78% by mass or less, 75% by mass or less, 70% by mass or less, 65% by mass or less, 60% by mass or less, 59% by mass or less, or 58.5% by mass or less. The lower limit of the content of the monomer other than n-octyl acrylate is 0.5% by mass or more, 1% by mass or more, 5% by mass or more, 10% by mass or more, 15% by mass or more, 20% by mass or more, 25% by mass or more, 30% by mass or more, 35% by mass or more, 38.5% by mass or more, 40% by mass or more, 45% by mass or more, 48.5% by mass or more, 50% by mass or more, 55% by mass or more, or 58.5% by mass or more. The range of the content of the monomer other than n-octyl acrylate may be any combination of the lower limit and upper limit values ​​described above.

[0021] <Polymerizable monomer having functional group (a2)> The polymerizable monomer (a2) having a functional group includes at least one of a polymerizable monomer having a carboxy group, a polymerizable monomer having a hydroxy group, and a polymerizable monomer having an amide group. The polymerizable monomer (a2) having a functional group is a radical polymerizable monomer having a functional group that can react with the curing agent (B) described below. A polymer network is formed by a crosslinking reaction between the functional group and the curing agent (B), and the cohesive strength and removability of the removable pressure-sensitive adhesive composition can be improved. The polymerizable monomer (a2) having a functional group is preferably a polymerizable monomer having a hydroxy group from the viewpoint of improving the removability of the removable pressure-sensitive adhesive composition.

[0022] The content of the polymerizable monomer (a2) having a functional group according to one embodiment is preferably 1.5 to 15 mass% or 1.5 to 14.5 mass% based on 100 mass% of the total polymerizable monomers. The upper limit of the content of the polymerizable monomer (a2) having a functional group is 15 mass% or less, 14.9 mass% or less, 14.8 mass% or less, 14.7 mass% or less, 14.6 mass% or less, or 14.5 mass% or less. The lower limit of the content of the polymerizable monomer (a2) having a functional group is 1.5 mass% or more, 2 mass% or more, 3 mass% or more, 4 mass% or more, 5 mass% or more, or 5.8 mass% or more. The range of the content of the polymerizable monomer (a2) having a functional group may be a combination of any of the lower and upper limits described above. When the content of the polymerizable monomer (a2) having a functional group is within the above-mentioned predetermined range, the adhesive strength during low-speed and high-speed peeling can be reduced. On the other hand, when the content of the polymerizable monomer (a2) having a functional group is less than 1.5% by mass or exceeds 15% by mass, the adhesive strength during low-speed and high-speed peeling increases.

[0023] Examples of the polymerizable monomer having a carboxy group include (meth)acrylic acid esters having a carboxy group, such as 2-carboxyethyl (meth)acrylate; and unsaturated carboxylic acids, such as (meth)acrylic acid, crotonic acid, maleic acid, itaconic acid, fumaric acid, citraconic acid, and mesaconic acid. These may be used alone or in combination of two or more. The polymerizable monomer having a carboxy group preferably includes acrylic acid.

[0024] The content of the polymerizable monomer having a carboxy group according to one embodiment is 0.1 to 0.8% by mass, preferably 0.2 to 0.8% by mass, based on 100% by mass of the total polymerizable monomers. The upper limit of the content of the polymerizable monomer having a carboxy group is 0.8% by mass or less, 0.75% by mass or less, 0.7% by mass or less, 0.65% by mass or less, or 0.6% by mass or less. The lower limit of the content of the polymerizable monomer having a carboxy group is 0.1% by mass or more, 0.2% by mass or more, 0.3% by mass or more, 0.4% by mass or more, or 0.5% by mass or more. The range of the content of the polymerizable monomer having a carboxy group may be any combination of the lower limit and upper limit values ​​described above. When the content of the polymerizable monomer having a carboxy group is within the above-mentioned predetermined range, the acid value of the (meth)acrylic polymer (A) can be set to a predetermined acid value, and the adhesive strength during low-speed and high-speed peeling can be reduced. If the content of the polymerizable monomer having a carboxy group exceeds 0.8% by mass, the adhesive strength during low-speed and high-speed peeling increases.

[0025] Examples of the polymerizable monomer having a hydroxy group include (meth)acrylic acid esters (hydroxyalkyl (meth)acrylates) having a hydroxy group, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. These may be used alone or in combination of two or more. The polymerizable monomer having a hydroxy group preferably includes at least one of 2-hydroxyethyl acrylate and 4-hydroxybutyl acrylate.

[0026] The content of the polymerizable monomer having a hydroxyl group according to one embodiment is preferably 1.5 to 15% by mass or 1.5 to 14.5% by mass based on 100% by mass of the total polymerizable monomers. The upper limit of the content of the polymerizable monomer having a hydroxyl group is 15% by mass or less, 14.9% by mass or less, 14.8% by mass or less, 14.7% by mass or less, 14.6% by mass or less, or 14.5% by mass or less. The lower limit of the content of the polymerizable monomer having a hydroxyl group is 1.5% by mass or more, 2% by mass or more, 3% by mass or more, 4% by mass or more, 5% by mass or more, or 5.8% by mass or more. The range of the content of the polymerizable monomer having a hydroxyl group may be any combination of the lower limit and the upper limit as described above. When the content of the polymerizable monomer having a hydroxyl group is within the above-mentioned predetermined range, the adhesive strength during low-speed and high-speed peeling can be reduced. On the other hand, if the content of the polymerizable monomer having a hydroxy group is less than 1.5% by mass or exceeds 15% by mass, the adhesive strength during low-speed and high-speed peeling increases.

[0027] Examples of the polymerizable monomer having an amide group include (meth)acrylamide, isopropyl(meth)acrylamide, dimethylaminopropyl(meth)acrylamide, and hydroxyethyl(meth)acrylamide. These may be used alone or in combination of two or more. The polymerizable monomer having an amide group preferably includes methacrylamide.

[0028] The content of the polymerizable monomer having an amide group according to one embodiment is 0.1 to 3 mass%, preferably 0.1 to 2 mass%, based on 100 mass% of the total polymerizable monomers. The upper limit of the content of the polymerizable monomer having an amide group is 3 mass% or less, 2.5 mass% or less, 2 mass% or less, 1.5 mass% or less, or 1 mass% or less. The lower limit of the content of the polymerizable monomer having an amide group is 0.1 mass% or more, 0.2 mass% or more, 0.3 mass% or more, 0.4 mass% or more, or 0.5 mass% or more. The range of the content of the polymerizable monomer having an amide group may be any combination of the above lower limit and upper limit.

[0029] <Polyalkylene glycol chain-containing mono(meth)acrylate (a3)> The (meth)acrylic polymer (A) according to one embodiment further comprises a polyalkylene glycol chain-containing mono(meth)acrylate (a3) ​​as a constituent unit, wherein the polyalkylene glycol chain-containing mono(meth)acrylate (a3) ​​having at least one hydroxyl group does not belong to the polymerizable monomer (a2) having a functional group.

[0030] The polyalkylene glycol chain-containing mono(meth)acrylate (a3) ​​may be a compound in which one of the multiple hydroxyl groups of the polyalkylene glycol is esterified as a (meth)acrylate. The polyalkylene glycol chain-containing mono(meth)acrylate (a3) ​​has an acryloyl group as a polymerizable group, and therefore can be copolymerized with the polymerizable monomer of the (meth)acrylic polymer (A) described above. The other hydroxyl group may remain as a hydroxyl group, or may be an alkyl ether such as methyl ether or ethyl ether, or a saturated carboxylic acid ester such as an acetate ester. Note that the polyalkylene glycol chain-containing mono(meth)acrylate (a3) ​​in which the other hydroxyl group remains as a hydroxyl group, i.e., the polyalkylene glycol chain-containing mono(meth)acrylate (a3) ​​having a hydroxyl group, does not belong to the polymerizable monomer (a2) having a functional group.

[0031] In the polyalkylene glycol chain-containing mono(meth)acrylate (a3), examples of the alkylene group of the polyalkylene glycol include, but are not limited to, an ethylene group, a propylene group, and a butylene group. The polyalkylene glycol may be a polyalkylene glycol having two or more types of alkylene groups in one molecule, such as polyethylene glycol-polypropylene glycol, polyethylene glycol-polybutylene glycol, and polypropylene glycol-polybutylene glycol. The polyalkylene glycol chain-containing mono(meth)acrylate (a3) ​​is preferably at least one compound having an average repeat number of 4 to 14 alkylene oxides constituting the polyalkylene oxide.

[0032] The polyalkylene glycol chain-containing mono(meth)(meth)acrylate (a3) ​​is preferably at least one selected from, for example, polyalkylene glycol mono(meth)acrylate, methoxypolyalkylene glycol (meth)acrylate, and ethoxypolyalkylene glycol (meth)acrylate.

[0033] More specific examples of polyalkylene glycol chain-containing mono(meth)acrylate (a3) ​​include polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, polybutylene glycol mono(meth)acrylate, methoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, methoxypolybutylene glycol (meth)acrylate, ethoxypolyethylene glycol (meth)acrylate, ethoxypolypropylene glycol (meth)acrylate, and ethoxypolybutylene glycol (meth)acrylate. These may be used alone or in combination of two or more. The polyalkylene glycol chain-containing mono(meth)acrylate (a3) ​​preferably contains methoxypolyethylene glycol methacrylate.

[0034] The content of the polyalkylene glycol chain-containing mono(meth)acrylate (a3) ​​according to one embodiment is 5 to 25% by mass, preferably 5 to 20% by mass, based on 100% by mass of the total polymerizable monomers. The upper limit of the content of the polyalkylene glycol chain-containing mono(meth)acrylate (a3) ​​is 25% by mass or less, 20% by mass or less, or 15% by mass or less. The lower limit of the content of the polyalkylene glycol chain-containing mono(meth)acrylate (a3) ​​is 5% by mass or more, or 10% by mass or more. The range of the content of the polyalkylene glycol chain-containing mono(meth)acrylate (a3) ​​may be any combination of the above lower limit and upper limit.

[0035] <Other monomers> The (meth)acrylic polymer (A) according to one embodiment may contain other monomers as constituent units.

[0036] Examples of other monomers include (meth)acrylic acid alkoxyalkyl esters such as 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, and 2-phenoxyethyl (meth)acrylate; (meth)acrylic acid aralkyl esters such as benzyl (meth)acrylate, 2-phenylethyl (meth)acrylate, and naphthylmethyl (meth)acrylate; (meth)acrylic acid aryl esters such as phenyl (meth)acrylate, tolyl (meth)acrylate, and naphthyl (meth)acrylate; and vinyl monomers such as styrene, α-methylstyrene, vinyl toluene, vinyl pyridine, vinyl pyrrolidone, vinyl acetate, and acrylonitrile.

[0037] <Method for producing (meth)acrylic polymer (A)> The (meth)acrylic polymer (A) can be produced by a known method, but is preferably produced by solution polymerization. Specifically, a solvent, a monomer, a polymerization initiator, etc. are generally heated to a reaction temperature of about 50 to 90°C under an inert gas atmosphere such as nitrogen gas, and polymerized for 4 to 12 hours. In the solution polymerization, it is preferable to use, for example, an ester-based solvent such as methyl acetate, ethyl acetate, or butyl acetate, a ketone-based solvent such as acetone, methyl ethyl ketone, or methyl isobutyl ketone, or a hydrocarbon-based solvent such as toluene, xylene, hexane, or heptane. These may be used alone or in combination of two or more.

[0038] The polymerization initiator may be any one capable of initiating radical polymerization, and any conventionally known polymerization initiator may be used.

[0039] Examples of the polymerization initiator include persulfates such as potassium persulfate, sodium persulfate, and ammonium persulfate; oil-soluble azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(isobutyric acid) dimethyl, and 1,1'-azobis(cyclohexane-1-carbonitrile); water-soluble azo compounds such as 2,2'-azobis[2-(2-imidazolin-2-yl)propane] and its salts, 2,2'-azobis(2-methylpropionamidine) and its salts, and 4,4'-azobis(4-cyanovaleric acid) and its salts; and organic peroxides such as benzoyl peroxide, cumene hydroperoxide, t-butyl hydroperoxide, t-butyl peroxy-2-ethylhexanoate, and t-butyl peroxyisobutyrate. These may be used alone or in combination of two or more kinds.

[0040] <Hardening agent (B)> The removable pressure-sensitive adhesive composition according to one embodiment further comprises a curing agent (B). When the removable pressure-sensitive adhesive composition comprises the curing agent (B), the cohesive strength of the removable pressure-sensitive adhesive composition is increased, improving the removable property.

[0041] The content of the curing agent (B) according to one embodiment is 0.3 to 8 parts by mass, preferably 0.3 to 5 parts by mass, and more preferably 0.3 to 4 parts by mass, based on 100 parts by mass of the (meth)acrylic polymer (A).

[0042] Examples of the curing agent (B) include isocyanate-based curing agents, epoxy-based curing agents, metal chelate-based curing agents, and aziridine-based curing agents. These may be used alone or in combination of two or more. The (meth)acrylic polymer (A) is preferably crosslinked by at least one of the curing agents (B). The curing agent (B) according to one embodiment is preferably an isocyanate-based curing agent.

[0043] Examples of the isocyanate-based curing agent include adducts of isocyanate compounds such as tolylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, tetramethylxylylene diisocyanate, naphthalene diisocyanate, triphenylmethane triisocyanate, and polymethylene polyphenyl isocyanate with polyol compounds such as trimethylolpropane, as well as biuret forms and isocyanurates thereof, and adducts of the above-mentioned isocyanate compounds with any of polyols such as polyether polyols, polyester polyols, acrylic polyols, polybutadiene polyols, and polyisoprene polyols; and compounds having two isocyanate groups in the molecule, such as allophanate forms thereof.

[0044] Examples of epoxy curing agents include epoxy resins obtained by reacting bisphenol A with epichlorohydrin, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, N,N-diglycidylaniline, N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane.

[0045] Examples of the metal chelate curing agent include coordination compounds of polyvalent metals such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium and zirconium with acetylacetone or ethyl acetoacetate.

[0046] Examples of the aziridine curing agent include N,N'-(4,4'-methylenediphenyl)bis(aziridine-1-carboxamide), 1,1'-isophthaloylbis(2-methylaziridine), tris(1-aziridinyl)phosphine oxide, 1,1'-hexamethylenebis(iminocarbonyl)bisaziridine, trimethylolpropane-tris(2-aziridinylpropionate), and 2,4,6-tris(1-aziridinyl)-1,3,5-triazine.

[0047] <Cure retarder (C)> The removable pressure-sensitive adhesive composition according to one embodiment further comprises a curing retarder (C).

[0048] The content of the curing retarder (C) according to one embodiment is 0.3 to 8 parts by mass, preferably 0.3 to 5 parts by mass, and more preferably 0.3 to 4 parts by mass, based on 100 parts by mass of the (meth)acrylic polymer (A).

[0049] The removable pressure-sensitive adhesive composition preferably further contains a keto-enol tautomer compound as a curing retarder (C). When a polyisocyanate compound such as a trifunctional or higher isocyanate compound is used as the curing agent (B), the keto-enol tautomer compound blocks the isocyanate group of the curing agent (B). This can suppress excessive viscosity increase and gelation of the removable pressure-sensitive adhesive composition after blending with the curing agent (B), and can extend the pot life of the removable pressure-sensitive adhesive composition.

[0050] Examples of the keto-enol tautomer compound include β-ketoesters such as methyl acetoacetate, ethyl acetoacetate, octyl acetoacetate, oleyl acetoacetate, lauryl acetoacetate, and stearyl acetoacetate, and β-diketones such as acetylacetone, 2,4-hexanedione, and benzoylacetone. These may be used alone or in combination of two or more. The keto-enol tautomer compound is preferably acetylacetone.

[0051] <Antistatic agent (D)> The removable pressure-sensitive adhesive composition according to one embodiment further contains an antistatic agent (D). The removable pressure-sensitive adhesive composition may contain an antistatic agent (D) in order to impart antistatic properties to the pressure-sensitive adhesive layer. This allows the surface protection film of the present invention to be suitably used as a surface protection film having antistatic properties.

[0052] The surface resistivity of the pressure-sensitive adhesive layer according to one embodiment is 1.0×10 +11 Ω / □ or less. Surface resistivity is an index showing the ease of electrical conduction per unit area of ​​a substance. A high surface resistivity indicates poor performance in dissipating static electricity generated by charging when peeling the adhesive layer from the adherend. On the other hand, a low surface resistivity indicates high performance in dissipating static electricity generated by charging when peeling the adhesive layer from the adherend. By making the surface resistivity of the adhesive layer as small as possible, the peeling charge generated when peeling the adhesive layer from the adherend is reduced, so that damage and failure of the adherend (for example, optical member) can be avoided. The antistatic property of the adhesive layer is not an essential property, and may be any property depending on the type of adherend.

[0053] The content of the antistatic agent (D) according to one embodiment is 0.05 to 10 parts by mass, preferably 0.05 to 7 parts by mass, and more preferably 1 to 4 parts by mass, based on 100 parts by mass of the (meth)acrylic polymer (A).

[0054] The antistatic agent (D) may be, for example, a pyridinium cation, an imidazolium cation, an ammonium cation, an alkali metal cation, or the like, or a hexafluorophosphate (PF6 - ), thiocyanate (SCN - ), alkylbenzene sulfonate (RC6H4SO3 - ), perchlorate (ClO4 - ), tetrafluoroborate (BF4 -), bis(fluorosulfonyl)imide salt (FSI), bis(trifluoromethanesulfonyl)imide salt (TFSI), tetrabutylammonium bis(trifluoromethanesulfonyl)imide salt, trifluoromethanesulfonate salt (TF), and other ionic compounds having an anion. These may be used alone or in combination of two or more. The antistatic agent (D) preferably contains lithium bis(trifluoromethanesulfonyl)imide (TFSI) or tetrabutylammonium bis(trifluoromethanesulfonyl)imide.

[0055] <Other additives> The removable adhesive composition of the present invention may contain various resins and additives as long as they do not affect the performance. Examples of additives include tackifiers, antioxidants, silane coupling agents, heat or light stabilizers, UV absorbers, leveling agents, defoamers, antibacterial agents, moisturizers, pigments, dyes, and fragrances. These may be used alone or in combination of two or more.

[0056] <Surface protection film> The surface protection film has a pressure-sensitive adhesive layer, which is a cured product of the removable pressure-sensitive adhesive composition of the present invention, on a substrate. The surface protection film can be produced, for example, by applying the removable pressure-sensitive adhesive composition to a substrate and drying it. The pressure-sensitive adhesive layer may be provided on at least one surface of the substrate. A release sheet may also be provided on the adhesive surface of the pressure-sensitive adhesive layer. The removable pressure-sensitive adhesive composition used in the surface protection film is as described above, and therefore a detailed description thereof will be omitted.

[0057] The adhesive layer is a layer having a slight adhesiveness for adhering the surface protection film to optical members such as a polarizing plate and a retardation plate. The adhesive layer may also have antistatic properties when the adherend is sensitive to static electricity. The reason for making the adhesive layer slightly adhesive is to make the surface protection film easy to peel off and to prevent adhesive residue when peeling it off from the optical member after use. When the surface protection film is attached to an optical member, it is preferable that the adhesive layer has sufficient transparency.

[0058] <Optical member with pressure-sensitive adhesive layer> The optical member with a pressure-sensitive adhesive layer according to an embodiment is obtained by laminating a pressure-sensitive adhesive layer obtained by curing the removable pressure-sensitive adhesive composition of the present invention on at least one surface of the optical member. Examples of the optical member include a polarizing film, a retardation film, an anti-reflection film, an anti-glare film, an ultraviolet absorbing film, an infrared absorbing film, an optical compensation film, and a brightness improving film. Examples of the display device equipped with the optical member include a liquid crystal display, an organic EL display, and a touch panel.

[0059] Examples of the liquid medium used when applying the removable adhesive composition include organic solvents such as toluene, xylene, hexane, heptane, etc.; ester solvents such as methyl acetate, ethyl acetate, butyl acetate, etc.; ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, etc.; halogenated hydrocarbon solvents such as dichloromethane, chloroform, etc.; ether solvents such as diethyl ether, methoxytoluene, dioxane, etc., and other hydrocarbon solvents. These may be used alone or in combination of two or more. Any liquid medium can be added to the removable adhesive composition to adjust the viscosity. The removable adhesive composition can also be heated to reduce the viscosity.

[0060] Examples of the substrate include cellophane, plastic sheets, rubber, foams, fabrics, rubber fabrics, resin-impregnated fabrics, glass plates, and wood. The substrate may be in the form of a plate or a film. Furthermore, the substrate may be made of a single material, or may be made of a multi-layer substrate made by laminating substrates of a plurality of materials. Furthermore, the substrate may have a surface that has been subjected to a release treatment. When the surface protective film is attached to an optical member, it is preferable that the substrate has sufficient transparency.

[0061] Examples of plastic sheets include polyvinyl alcohol films, triacetyl cellulose films, polypropylene, polyethylene, polycycloolefin, ethylene-vinyl acetate copolymer and other polyolefin resin films, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate and other polyester resin films, polyvinyl chloride and other vinyl resin films, polycarbonate resin films, polynorbornene resin films, polyarylate resin films, acrylic resin films, polyphenylene sulfide resin films, polystyrene resin films, polyamide resin films, polyimide resin films, epoxy resin films, etc. These may be used alone or in combination of two or more.

[0062] A resin film such as a polyester film can be used as the release sheet (separator) that protects the adhesive surface of the adhesive layer. The surface of the release sheet that meets the adhesive surface of the adhesive layer is subjected to a release treatment using a silicone-based or fluorine-based release agent.

[0063] Examples of the application method of the removable pressure-sensitive adhesive composition include a Mayer bar, an applicator, a brush, a spray, a roller, a gravure coater, a die coater, a lip coater, a comma coater, a knife coater, a reverse coater, and a spin coater. Examples of the drying method include hot air drying, infrared rays, and a reduced pressure method. The drying conditions can be appropriately changed depending on the cured form, film thickness, and type of solvent of the removable pressure-sensitive adhesive composition, and may be, for example, hot air drying at 60 to 130°C.

[0064] The thickness of the pressure-sensitive adhesive layer according to one embodiment is from 1 to 200 μm, and preferably from 3 to 100 μm.

[0065] <Production of removable adhesive composition> Table 1 shows the raw material composition and physical properties of the (meth)acrylic polymer (A) in Production Examples 1 to 6. Table 2 shows the raw material composition and physical properties of the (meth)acrylic polymer (A) in Production Examples 7 to 13. Table 3 shows the raw material composition and physical properties of the (meth)acrylic polymer (A) in Production Examples 14 to 17. Table 4 shows the raw material composition and test results of the removable pressure-sensitive adhesive compositions in Examples 1 to 7. Table 5 shows the raw material composition and test results of the removable pressure-sensitive adhesive compositions in Examples 8 to 15. Table 6 shows the raw material composition and test results of the removable pressure-sensitive adhesive compositions in Comparative Examples 1 to 4.

[0066] [Table 1] (Explanation of Abbreviations) · Component (a1): represents an alkyl group-containing unsaturated monomer (a1) having an alkyl group having 1 to 18 carbon atoms. · Component (a2): represents a polymerizable monomer (a2) having a functional group. · Component (a3): Polyalkylene glycol chain-containing mono(meth)acrylate (a3). ·NOAA: n-Octyl acrylate 2EHA: 2-Ethylhexyl acrylate MPEGMA: Methoxypolyethyleneglycol methacrylate 4HBA: 4-Hydroxybutyl acrylate ·HEA: 2-Hydroxyethyl acrylate AAc: Acrylic acid mAM: methacrylamide

[0067] [Table 2] (Explanation of Abbreviations) See Table 1 for explanation of abbreviations

[0068] [Table 3] (Explanation of Abbreviations) -See Table 1 for explanation of abbreviations

[0069] [Table 4] (Explanation of Abbreviations) Hardener (B): Isocyanate-based hardener (manufactured by Saiden Chemical Industries, Ltd.) Li-TFSI: Lithium bis(trifluoromethanesulfonyl)imide FC-4400: Tetrabutylammonium bis(trifluoromethanesulfonyl)imide (3M) - Adhesion strength at low peel speed (gf / 25mm) 0.3m / min: See Test 1 below Adhesion strength at high speed peeling (gf / 25mm) 30m / min: See Test 1 below Wettability (sec): See Test 2 below Surface resistivity (Ω / □): See Test 3 below

[0070] [Table 5] (Explanation of Abbreviations) See Table 4 for explanation of abbreviations

[0071] [Table 6] (Explanation of Abbreviations) See Table 4 for explanation of abbreviations

[0072] <Production Example 1: Production method for (meth)acrylic polymer (A)> With reference to Table 1, the method for producing the (meth)acrylic polymer (A) of Production Example 1 will be described. 45 parts of ethyl acetate, 5 parts of acetone, and 0.05 parts of a polymerization initiator (azobisisobutyronitrile) were charged into a reaction apparatus equipped with a stirrer, a thermometer, a successive dropping device, and a reflux condenser. Meanwhile, a monomer-solvent mixture consisting of 98.5 parts of n-octyl acrylate, 1.5 parts of 4-hydroxybutyl acrylate, and 30 parts of ethyl acetate was prepared in another container. The reaction apparatus was heated to 73°C while stirring, and the monomer-solvent mixture weighed in another container was dropped over 75 minutes, and a polymerization reaction was carried out at 80°C for 7 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain a (meth)acrylic polymer (A) solution with a solid content of 44.0% by mass.

[0073] <Production Examples 2 to 13: Production Methods for (Meth)acrylic Polymer (A)> The (meth)acrylic polymers (A) of Production Examples 2 to 13 were produced based on the raw material compositions in Tables 1 and 2 and the same production method as Production Example 1, so detailed explanations are omitted. The acid value (mg KOH / g) of the (meth)acrylic polymer (A) of Production Example 11 was 6.22 (calculated value).

[0074] <Production Examples 14 to 17: Production Method for (Meth)acrylic Polymer (A)> Detailed explanations are omitted because the (meth)acrylic polymers (A) of Production Examples 14 to 17 were produced based on the raw material composition in Table 3 and the same production method as Production Example 1. The acid value (mg KOH / g) of the (meth)acrylic polymer (A) of Production Example 17 was 7.78 (calculated value).

[0075] <Example 1: Method for producing removable adhesive composition> A method for producing the removable adhesive composition of Example 1 will be described with reference to Table 4. To 100 parts of the solid content of the (meth)acrylic polymer (A) solution of Production Example 1, 3.4 parts in solid content of an isocyanate-based curing agent (manufactured by Saiden Chemical Industry Co., Ltd.) as the curing agent (B) and 4.0 parts of acetylacetone as the curing retarder (C) were added and thoroughly mixed to obtain a removable adhesive composition.

[0076] <Example 1: Method for manufacturing a surface protective film> The removable adhesive composition of Example 1 was directly applied to a 38 μm thick polyethylene terephthalate (PET) film substrate. The solvent was then removed by drying at 110° C. to form an adhesive layer having a thickness of 15 μm. A silicone resin-coated polyester film (release sheet) was coated on the surface on which the adhesive layer was formed to prepare a surface protection film. The surface protection film thus prepared was then aged at 40° C. for 3 days to obtain samples for each test.

[0077] <Examples 2 to 15: Method for producing removable adhesive composition> The removable pressure sensitive adhesive compositions of Examples 2 to 15 were produced based on the raw material compositions in Tables 4 and 5 and the same production method as in Example 1, so detailed explanations are omitted. In Example 9, 1 part of lithium bis(trifluoromethanesulfonyl)imide was added as the antistatic agent (D). In Example 10, 4 parts of tetrabutylammonium bis(trifluoromethanesulfonyl)imide was added as the antistatic agent (D).

[0078] <Examples 2 to 15: Method for producing surface protective film> The surface protection films of Examples 2 to 15 were produced based on the same production method as in Example 1, and therefore detailed explanations are omitted.

[0079] <Comparative Examples 1 to 4: Methods for producing removable adhesive compositions> The removable pressure-sensitive adhesive compositions of Comparative Examples 1 to 4 were produced based on the raw material compositions in Table 6 and the same production method as in Example 1, so detailed explanations are omitted.

[0080] <Comparative Examples 1 to 4: Methods for producing surface protective films> The surface protection films of Comparative Examples 1 to 4 were produced based on the same production method as in Example 1, and therefore detailed explanations are omitted.

[0081] <Test Method> The surface protection films of Examples 1 to 15 and Comparative Examples 1 to 4 were used to carry out the following Tests 1 to 3.

[0082] (Test 1: Adhesive strength measurement) A test piece was prepared by cutting the sample (surface protection film) to a width of 25 mm and a length of 70 mm. The release sheet was peeled off from the test piece, and the test piece was attached to the surface of the PET substrate, and pressed with a 2 kg roll. The test piece was then left for 24 hours in an atmosphere of 23°C and 50% humidity. After leaving the test piece, the adhesive strength was measured using a tensile tester in accordance with JIS Z-0237:2000 at a tensile speed of 0.3 m / min or 30 m / min and a peel angle of 180°. [Evaluation Criteria] - Adhesive strength at low peel speed (gf / 25mm), pulling speed 0.3m / min ○:2.0~9.9gf / 25mm ×:10.0gf / 25mm or more - Adhesive strength at high speed peeling (gf / 25mm), pulling speed 30m / min ○: Less than 100gf / 25mm ×:100gf / 25mm or more

[0083] (Test 2: Checking wettability) The sample (surface protection film) was cut to 100 mm x 100 mm to prepare a test piece. The release sheet was peeled off from the test piece, and the test piece was placed on the PET substrate, and the center of the test piece was lightly pressed with a finger. The time from pressing the center of the test piece until the entire surface of the test piece was wetted and spread over the PET was measured. [Evaluation Criteria] ○: Less than 12.0 seconds ×: 12.0 seconds or more

[0084] (Test 3: Measurement of surface resistivity) The release sheet was peeled off from the test piece (surface protection film) to expose the pressure-sensitive adhesive layer, and the surface resistivity of the pressure-sensitive adhesive layer was measured using a resistivity meter.

[0085] <Test Results> With reference to Tables 4 to 6 above, the test results of Examples 1 to 15 and Comparative Examples 1 to 4 will be described.

[0086] As shown by the results of Tests 1 and 2, Examples 1 to 15 showed excellent adhesive strength and wettability during both low-speed and high-speed peeling. Examples 9 and 10 showed that the adhesive layer had excellent antistatic properties. On the other hand, Comparative Examples 1 to 4 did not show excellent adhesive strength and wettability during low-speed and high-speed peeling, as shown by the results of Tests 1 and 2.

[0087] According to the test results, in Comparative Example 1, the content of n-octyl acrylate was less than the lower limit specified in the present invention, so the adhesive strength at low peel speed was high. In addition, the wettability was reduced. In Comparative Example 2, the content of the polymerizable monomer (a2) having a functional group exceeded the upper limit specified in the present invention, so the polarity of the adhesive layer was high and the intermolecular force with the adherend surface was strong, so the adhesive strength at low and high peel speeds was high. In Comparative Example 3, the content of the polymerizable monomer (a2) having a functional group was less than the lower limit specified in the present invention, so the crosslinking density was low and the film was soft, so the adhesive strength at low and high peel speeds was high. In Comparative Example 4, the acid value of the (meth)acrylic polymer (A) exceeded the upper limit specified in the present invention, so the polarity of the adhesive layer was high and the intermolecular force with the adherend surface was strong, so the adhesive strength at low and high peel speeds was high.

[0088] As described above, the removable pressure-sensitive adhesive composition of the present invention has the remarkable effects of being excellent in wettability and capable of reducing adhesive strength during low-speed and high-speed peeling.

[0089] The invention is not limited to the above-described embodiment, and various modifications and variations are possible within the scope of the gist of the invention.

Claims

1. The (meth)acrylic polymer (A) contains, as structural units, an alkyl group-containing unsaturated monomer (a1) having an alkyl group having 1 to 18 carbon atoms, and 1.5 to 14.5 mass % of a polymerizable monomer (a2) having a functional group, The alkyl group-containing unsaturated monomer (a1) having an alkyl group having 1 to 18 carbon atoms contains 20 to 85% by mass of n-octyl acrylate, The (meth)acrylic polymer (A) has an acid value of 7.5 mg KOH / g or less, The (meth)acrylic polymer (A) further contains 5 to 25% by mass of a polyalkylene glycol chain-containing mono(meth)acrylate (a3) ​​as a constituent unit, wherein the polyalkylene glycol chain-containing mono(meth)acrylate (a3) ​​having at least one hydroxy group does not belong to the polymerizable monomer (a2) having a functional group, The polyalkylene glycol chain-containing mono(meth)acrylate (a3) ​​is methoxypolyethylene glycol methacrylate. A removable pressure-sensitive adhesive composition.

2. The polymerizable monomer (a2) having a functional group contains 0.1 to 0.8 mass% of a polymerizable monomer having a carboxy group. The removable pressure-sensitive adhesive composition according to claim 1 .

3. The (meth)acrylic polymer (A) contains 1.5 to 2 mass % of the polymerizable monomer (a2) having the functional group as a constituent unit, The alkyl group-containing unsaturated monomer (a1) having an alkyl group having 1 to 18 carbon atoms contains 20 to 50% by mass of n-octyl acrylate. The removable pressure-sensitive adhesive composition according to claim 1 .

4. The alkyl group-containing unsaturated monomer (a1) having an alkyl group having 1 to 18 carbon atoms further contains 38.5 to 78 mass% of 2-ethylhexyl acrylate. The removable pressure-sensitive adhesive composition according to claim 3.

5. The alkyl group-containing unsaturated monomer (a1) having an alkyl group having 1 to 18 carbon atoms further contains 0.5 to 78 mass% of 2-ethylhexyl acrylate. The removable pressure-sensitive adhesive composition according to claim 1 .

6. The polymerizable monomer (a2) having a functional group includes a polymerizable monomer having a hydroxy group. The removable pressure-sensitive adhesive composition according to claim 1 .

7. The polymerizable monomer (a2) having a functional group further includes a polymerizable monomer having a carboxy group or a polymerizable monomer having an amide group. The removable pressure-sensitive adhesive composition according to claim 1 .

8. The polymerizable monomer (a2) having a functional group contains 0.1 to 3 mass % of a polymerizable monomer having an amide group. The removable pressure-sensitive adhesive composition according to claim 1 .

9. Further comprising a curing agent (B), The curing agent (B) includes an isocyanate-based curing agent. The removable pressure-sensitive adhesive composition according to claim 1 .

10. Further comprising a cure retarder (C), The cure retarder (C) comprises a keto-enol tautomer compound; The removable pressure-sensitive adhesive composition according to claim 9 .

11. Further comprising an antistatic agent (D), The removable pressure-sensitive adhesive composition according to claim 1 .

12. A substrate; and a pressure-sensitive adhesive layer comprising the removable pressure-sensitive adhesive composition according to any one of claims 1 to 11 provided on at least one surface of the substrate. Surface protection film.

13. The surface resistivity of the pressure-sensitive adhesive layer is 1.0×10 11 Ω / □ or less, The surface protective film according to claim 12.

14. An optical member; and a pressure-sensitive adhesive layer comprising the removable pressure-sensitive adhesive composition according to any one of claims 1 to 11 and provided on at least one surface of the optical member. An optical component with an adhesive layer.

Citation Information

Patent Citations

  • Ultraviolet curing pressure-sensitive adhesive for polaroid

    CN113549412A

  • Pressure-sensitive adhesive

    JP1988225677A

  • Method for adjusting peel strength, adhesive layer for optical member and method for producing the same, optical member with adhesive and image display device

    JP2005344014A

  • Adhesive composition and film for optical member having adhesive layer

    JP2014114325A

  • Self-wetting adhesive composition

    JP2016527341A